IDENTIFIKASI INBREEDING PADA JALAK PUTIH (STURNUS MELANOPTERUS DAUDIN 1800) DI PUSAT PENYELAMATAN SATWA CIKANANGA, JAWA BARAT - Bangkit Maulana; Burhanuddin Masy'ud; Ani Mardiastuti (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Black winged starling is a critically endangered species in IUCN red list data book. Decreasing in number of population drive to do exsitu conservation. One of exsitu conservation institution with black winged starling conservation program is Cikananga Animal Rescue Center (CARC).CARC breeds the Black winged starling in captive and reintroduction it in several place. There risk of inbreeding in animal breeding by captive if the breeding was uncontrolled. Inbreeding decreasing animal life survival and cause an abnormality in growth. This research aimed to identify inbreeding on Black-winged Starling. Identification the inbreeding aimed by tracing Black-winged Starling’s studbook and morfometry size approach. There was no inbreeding based on studbook approach. Inbreeding approach by abnormality in growth show there is a different in growth performance in head width and third digit length on first, second and third generation. Keywords: black winged starling, Cikananga, inbreeding